Aspidistra leipingensis (Asparagaceae), a new species from Guangxi, China - Ding, Zhong-Biao; Li, Shuang-Long; Li, Ren-Kun; Zeng, Yong; Dun, Chun-Yao; Lin, Chun-Rui (Phytotaxa, 2024)
Aspidistra leipingensis, a new species of Asparagaceae from Guangxi, southern China, is described and illustrated. The new species is morphologically similar to A. punctatoides, but can be distinguished by its shorter leaf blade and petiole, longer perianth tube, stamens inserted in the lower part of the perianth tube, stigma hemispherical shape, upper surface convex and glabrous. Colour plate and line drawing of the new species are provided.